2009
DOI: 10.1016/j.str.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Structure of HIV-1 Reverse Transcriptase with the Inhibitor β-Thujaplicinol Bound at the RNase H Active Site

Abstract: Summary Novel inhibitors are needed to counteract the rapid emergence of drug-resistant HIV variants. HIV-1 reverse transcriptase (RT) has both DNA polymerase and RNase H (RNH) enzymatic activities, but approved drugs that inhibit RT target the polymerase. Inhibitors that act against new targets, like RNH, would be effective against all of the current drug-resistant variants. Here, we present 2.80 Å and 2.04 Å resolution crystal structures of an RNH inhibitor, β-thujaplicinol, bound at the RNH active site of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
193
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(203 citation statements)
references
References 53 publications
9
193
1
Order By: Relevance
“…For the ␤-thujaplicinol anion, we speculate that its negative charge may not be as readily available for coordinate bond formation due to its delocalization across the tropolone ring, carbonyl, and hydroxyl groups. This is generally consistent with the perspective of Himmel et al (22), with the exception that they suggest that ␤-thujaplicinol binds as a neutral molecule.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For the ␤-thujaplicinol anion, we speculate that its negative charge may not be as readily available for coordinate bond formation due to its delocalization across the tropolone ring, carbonyl, and hydroxyl groups. This is generally consistent with the perspective of Himmel et al (22), with the exception that they suggest that ␤-thujaplicinol binds as a neutral molecule.…”
Section: Discussionsupporting
confidence: 91%
“…The existence of such a complex has been postulated in the context of ␤-thujaplicinol (22). It is conceivable that the benzothiophene moiety of GSK5750 contributes to this interaction by directly binding to the substrate, perhaps by intercalation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-thujaplicinol, a selective inhibitor of HIV RT, is a typical metal chelator [33]. Our study demonstrated that it binds to two Mg [21].…”
Section: Metal-chelating Compoundsmentioning
confidence: 66%